3D printing phase change anti-counterfeiting label and preparation method thereof

CN118762600BActive Publication Date: 2026-10-27QINGDAO UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410793927.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2026-10-27
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

[0007]有鉴于此,本发明提供了一种3D打印相变防伪标签及其制备方法,解决了现有防伪标签制备成本较高、安全系数较低、相变材料3D打印时易泄露的问题

Benefits of technology

[0026](1)本发明提供的3D打印相变防伪标签中的加密信息通过3D打印实现,因此可以实现不同样式加密信息的书写,较传统拼凑式相变防伪技术具有编程灵活、制造成本低、加密信息更加复杂、可实现小批量定制化的优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118762600B_ABST
    Figure CN118762600B_ABST
Patent Text Reader

Abstract

The application discloses a 3D printing phase change anti-fake label and a preparation method thereof, and belongs to the technical field of 3D printing anti-fake materials. The 3D printing phase change anti-fake label comprises a bottom film, an encrypted information layer and a cover layer. The bottom film is a cellulose film containing opaque color heat-conducting fillers. The encrypted information layer is obtained by 3D printing of phase change slurry on the bottom film. The phase change slurry comprises phase change microcapsules, cellulose and opaque color heat-conducting fillers. The cover layer comprises polydimethylsiloxane and opaque color heat-conducting fillers. The 3D printing phase change anti-fake label can realize writing of different styles of encrypted information, the encrypted information is more complex, small-batch customization can be realized, the phase change material is not easy to leak, the temperature window for observing the encrypted information is small, the encrypted information can be observed only by an infrared camera, and the safety coefficient is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of 3D printing anti-counterfeiting materials technology, and in particular to a 3D printed phase change anti-counterfeiting label and its preparation method. Background Technology

[0002] The information disclosed in the background section of this invention is intended only to enhance the understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Traditional anti-counterfeiting labels have a simple anti-counterfeiting structure. To improve the reliability of anti-counterfeiting labels, researchers have developed a variety of anti-counterfeiting technologies such as watermarks, graphic codes, structural colors, molecular tags, and fluorescence. However, these technologies all have drawbacks such as high cost, difficulty in writing / reading information, and low security.

[0004] Anti-counterfeiting technologies typically rely on factors such as light, heat, and force to store or retrieve encrypted information. Among these, heat-controlled anti-counterfeiting technologies have greater advantages in terms of the accuracy of encrypted information, manufacturing costs, and service life. However, the current technical means for preparing anti-counterfeiting labels through heat control are limited, and the ability to write encrypted information is also restricted.

[0005] Phase change energy storage refers to storing energy through latent heat by utilizing the phase change process of phase change materials. It boasts advantages such as good energy storage performance, high stability, and long lifespan, making it a promising application for encrypting information in thermal anti-counterfeiting labels. While the development of 3D printing technology has significantly improved the complexity and precision of encrypted information in anti-counterfeiting labels, phase change materials are prone to leakage, making it difficult to use 3D printing technology to write encrypted information. This severely limits the precision of phase change anti-counterfeiting labels, hindering the fabrication of complex anti-counterfeiting labels.

[0006] Furthermore, existing phase change anti-counterfeiting materials allow the encrypted information to be observed with the naked eye at specific temperatures, which reduces the anti-counterfeiting security level. Therefore, providing a 3D-printed phase change anti-counterfeiting label with high security and the ability to store a large amount of information is an urgent problem to be solved. Summary of the Invention

[0007] In view of this, the present invention provides a 3D printed phase change anti-counterfeiting label and its preparation method, which solves the problems of high preparation cost, low security factor and easy leakage of phase change material during 3D printing of existing anti-counterfeiting labels.

[0008] In a first aspect, the present invention provides a 3D printed phase change anti-counterfeiting label, comprising a bottom film, an encrypted information layer, and a cover layer;

[0009] The underlying film is a cellulose membrane containing an opaque, thermally conductive filler.

[0010] The encrypted information layer is obtained by 3D printing a phase change slurry onto a bottom film; the phase change slurry includes phase change microcapsules, cellulose, and opaque thermally conductive filler.

[0011] The capping layer comprises polydimethylsiloxane and an opaque thermally conductive filler.

[0012] Preferably, the cellulose of the cellulose membrane of the bottom film and the cellulose of the encryption information layer are selected from one or more of bacterial cellulose, methylcellulose, ethylcellulose, or microfibrillated cellulose.

[0013] Preferably, the opaque thermally conductive filler of the bottom film, the encrypted information layer, and the cover layer is selected from one or more of silicon carbide, graphene microsheets, silicon oxide, graphite powder, carbon nanotubes, beryllium oxide, aluminum nitride, carbon black, or carbon fiber.

[0014] Preferably, the cellulose type of the cellulose membrane of the bottom film is the same as that of the encryption information layer, and the opaque thermally conductive filler of the bottom film, the encryption information layer, and the cover layer are of the same type.

[0015] Preferably, the phase change microcapsules are selected from one or more of paraffin microcapsules, polyethylene glycol microcapsules, octadecane microcapsules, or eicosane microcapsules.

[0016] Preferably, the phase change slurry comprises 75-85 parts of phase change microcapsules, 5-15 parts of cellulose, and 5-15 parts of opaque thermally conductive filler.

[0017] Preferably, the content of the opaque thermally conductive filler in the bottom film and the cover layer is 10-30 wt%.

[0018] Preferably, the thickness of the 3D printed phase change anti-counterfeiting label is 50-250 μm, the thickness of the bottom film is 10-50 μm, and the thickness of the encryption information layer is 1 / 2 to 1 / 3 of the thickness of the 3D printed phase change anti-counterfeiting label.

[0019] Secondly, the present invention provides a method for preparing the above-mentioned 3D printed phase change anti-counterfeiting label, comprising the following steps:

[0020] A. Disperse an opaque thermally conductive filler in an aqueous cellulose dispersion, and prepare a bottom film by scraping or spin coating and drying.

[0021] B. Disperse phase change microcapsules and opaque thermally conductive fillers in cellulose aqueous dispersion and stir to mix evenly to obtain phase change slurry; use 3D printing technology to print an encrypted information layer on the surface of the bottom film of the phase change slurry.

[0022] C. After uniformly mixing the opaque thermally conductive filler and polydimethylsiloxane, coat and smooth the surface of the bottom film and the encrypted information layer, and heat and cure to obtain the cover layer.

[0023] Preferably, the concentration of the cellulose aqueous dispersion in steps A and B is 0.5–3 wt%.

[0024] Preferably, in the step of preparing the underlying film by scraping or spin coating and drying, the drying temperature is 50-100°C; in the step of obtaining the cover layer by heating and curing, the heating and curing temperature is 80-100°C and the heating and curing time is 1-4 hours.

[0025] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0026] (1) The encrypted information in the 3D printed phase change anti-counterfeiting label provided by the present invention is realized by 3D printing, so different styles of encrypted information can be written. Compared with the traditional piecemeal phase change anti-counterfeiting technology, it has the advantages of flexible programming, low manufacturing cost, more complex encrypted information, and small batch customization.

[0027] (2) The encrypted information layer of the present invention uses phase change microcapsules, which are less likely to cause leakage of phase change materials; at the same time, by utilizing the excellent energy storage density of phase change materials during the phase change process, encrypted information can be observed at a specific temperature, which has higher resolution.

[0028] (3) The presence of the opaque thermally conductive filler in the 3D-printed phase change anti-counterfeiting label provided by this invention makes the heat transfer speed in the phase change anti-counterfeiting label faster and the temperature window for observing encrypted information smaller; moreover, the opaque thermally conductive filler has obvious opacity, which can cover the storage of encrypted information at any temperature, and the encrypted information can only be observed through an infrared camera. Therefore, the 3D-printed phase change anti-counterfeiting label provided by this invention has a high security factor. Attached Figure Description

[0029] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments and descriptions of the invention are used to explain the invention and do not constitute an undue limitation thereof. Obviously, those skilled in the art can obtain other drawings based on these drawings without any inventive effort.

[0030] Figure 1 This is a schematic diagram of the structure of the 3D printed phase change anti-counterfeiting label of the present invention;

[0031] Figure 2 This is a schematic diagram illustrating the working principle of the 3D-printed phase change anti-counterfeiting label of this invention;

[0032] Figure 3 The images shown are infrared imaging (a) and barcode scanning results (b) of the barcode phase change anti-counterfeiting label film of Embodiment 1 of the present invention at 45°C.

[0033] Figure 4 The results of scanning the QR code on the infrared imaging photos of the QR code phase change anti-counterfeiting label film of Embodiment 2 of the present invention at 30°C (a), 60°C (b) and 48°C are shown in (c).

[0034] Figure 5 This is a photo taken with a regular camera at 48°C of the QR code phase-change anti-counterfeiting label film of Embodiment 2 of the present invention;

[0035] Figure 6 These are infrared images of the multi-stage phase change anti-counterfeiting label film of Embodiment 3 of the present invention at 35°C (a) and 50°C (b);

[0036] Figure 7 These are the DSC curves of the low-temperature microcapsules, low-temperature phase change slurry, high-temperature microcapsules, and high-temperature phase change slurry of Embodiment 3 of the present invention. Detailed Implementation

[0037] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0038] This invention provides a 3D-printed phase change anti-counterfeiting label, comprising a base film, an encrypted information layer, and a cover layer;

[0039] The underlying film is a cellulose membrane containing an opaque, thermally conductive filler.

[0040] The encrypted information layer is obtained by 3D printing a phase change slurry onto a bottom film; the phase change slurry includes phase change microcapsules, cellulose, and opaque thermally conductive filler.

[0041] The capping layer comprises polydimethylsiloxane and an opaque thermally conductive filler.

[0042] The 3D-printed phase change anti-counterfeiting label provided by this invention has a three-layer structure, as shown in the schematic diagram below. Figure 1 As shown in the diagram. The bottom film serves to carry and conceal encrypted information, the encrypted information layer stores encrypted information, and the cover layer enhances the flexibility of the anti-counterfeiting label and conceals encrypted information.

[0043] The encrypted information layer contains phase change microcapsules, which effectively protect the phase change material from leakage during 3D printing. Since the phase change microcapsules are used as the encrypted information material in the anti-counterfeiting label film, they are prone to breakage during the bending process of the anti-counterfeiting label. This invention uses cellulose as a toughness-enhancing agent for the encrypted information layer. Cellulose has a soft, long-chain structure and good flexibility.

[0044] The principle of the 3D-printed phase change anti-counterfeiting label provided by this invention is as follows: The 3D-printed phase change anti-counterfeiting label of this invention has the characteristics of high-temperature concealment and low-temperature concealment. The phase change material of the encrypted information layer can absorb or release energy within a specific temperature range without changing its temperature, thereby creating a temperature difference with the surrounding materials. Thus, the anti-counterfeiting information is revealed at a specific temperature. A schematic diagram of the working principle is shown below. Figure 2 As shown, the addition of opaque thermally conductive filler makes the heat transfer in the phase change anti-counterfeiting label faster and the temperature window for observing the encrypted information smaller; moreover, the opaque thermally conductive filler has obvious opacity, which can cover the storage of encrypted information at any temperature, and the encrypted information can only be observed through an infrared camera. Therefore, the 3D printed phase change anti-counterfeiting label provided by this invention has a high security factor.

[0045] In this invention, the cellulose in the cellulose membrane of the bottom film and the cellulose in the encryption information layer are selected from one or more of bacterial cellulose, methylcellulose, ethylcellulose, or microfibrillated cellulose. The cellulose in the bottom film can be made into a cellulose membrane, thus playing a certain load-bearing role. Cellulose has good self-healing ability. The presence of cellulose in the encryption information layer can enhance the interfacial interaction between the encryption information layer and the bottom film, as well as between the encryption information layer and the cover layer, thereby making the bonding between the layers of the prepared 3D printed phase change anti-counterfeiting label tighter and preventing detachment. This invention does not impose special limitations on the size of the cellulose; the preferred diameter is 10–100 nm, and the preferred length is greater than 20 μm.

[0046] In this invention, the opaque thermally conductive filler in the bottom film, the encrypted information layer, and the capping layer is selected from one or more of silicon carbide, graphene microsheets, silicon oxide, graphite powder, carbon nanotubes, beryllium oxide, aluminum nitride, carbon black, or carbon fiber. The opaque thermally conductive filler can both narrow the phase transition temperature window and provide good masking. This invention does not impose special limitations on the particle size of the opaque thermally conductive filler; preferably, it is 10–25 μm.

[0047] In this invention, the cellulose type of the cellulose membrane in the bottom film is the same as that in the encryption information layer, and the opaque thermally conductive filler type of the bottom film, the encryption information layer, and the cover layer is the same. This design facilitates further enhancement of the bonding between the layers.

[0048] In this invention, the phase change microcapsules are selected from one or more of paraffin microcapsules, polyethylene glycol microcapsules, octadecane microcapsules, or eicosane microcapsules. This invention does not impose any special limitations on the preparation method of the phase change microcapsules; any preparation method well-known in the art can be used. In this invention, the phase change temperature of the phase change microcapsules is 15–100°C, more preferably 30–80°C, and even more preferably 35–60°C. Multi-level anti-counterfeiting effects displaying different encrypted information at different temperatures can be achieved using various phase change microcapsules with different phase change temperatures, further enhancing anti-counterfeiting security. This invention does not impose any special limitations on the shape, particle size, etc., of the phase change microcapsules; the particle size is preferably 10–25 μm. The mass fraction of the phase change material in the phase change microcapsules is preferably 80–90 wt%.

[0049] In this invention, the phase change slurry comprises 75-85 parts phase change microcapsules, 5-15 parts cellulose, and 5-15 parts opaque thermally conductive filler; preferably, the phase change slurry comprises 75-80 parts phase change microcapsules, 10-15 parts cellulose, and 10-15 parts opaque thermally conductive filler. Phase change materials outside the above ranges may cause problems such as blurred display, breakpoints, or adhesion of encrypted information.

[0050] In this invention, the content of the opaque thermally conductive filler in the bottom film and the cover layer is 10-30 wt%. If the amount of opaque thermally conductive filler added is too small, its thermal conductivity and masking effects will not be fully utilized; if the amount added is too large, it will lead to a decrease in the flexibility of the 3D printed phase change anti-counterfeiting label, making it prone to breakage during preparation, transportation, and use.

[0051] In this invention, the thickness of the 3D-printed phase-change anti-counterfeiting label is 50–250 μm, and the thickness of the bottom film is 10–50 μm. The bottom film is made as thin as possible while ensuring it is opaque to guarantee the thermal resolution of the encrypted information layer. The thickness of the encrypted information layer is 1 / 2 to 1 / 3 of the thickness of the 3D-printed phase-change anti-counterfeiting label to ensure sufficient temperature difference between the encrypted information layer and other layers to display the anti-counterfeiting information. This invention does not impose special limitations on the thickness of the overlay layer; it only needs to ensure that the encrypted information layer is completely covered.

[0052] This invention also provides a method for preparing the above-mentioned 3D printed phase change anti-counterfeiting label, comprising the following steps:

[0053] A. Disperse opaque thermally conductive filler in an aqueous cellulose dispersion, and prepare a bottom film by scraping or spin coating and drying;

[0054] B. Disperse phase change microcapsules and opaque thermally conductive fillers in cellulose aqueous dispersion and stir to mix evenly to obtain phase change slurry; use 3D printing technology to print an encrypted information layer on the surface of the bottom film of the phase change slurry.

[0055] C. After uniformly mixing the opaque thermally conductive filler and polydimethylsiloxane, coat and smooth the surface of the bottom film and the encrypted information layer, and heat and cure to obtain the cover layer.

[0056] In this invention, the concentration of the cellulose aqueous dispersion in steps A and B is 0.5–3 wt%.

[0057] In this invention, the viscosity of the polydimethylsiloxane in step C is 3000-5000 cP.

[0058] This invention does not impose any special restrictions on the method of blade coating or spin coating; any commonly used method in the art for preparing cellulose membranes can be used.

[0059] This invention does not impose special restrictions on the temperature, time, or stirring speed for uniform mixing; it only requires ensuring that the materials are fully and evenly mixed.

[0060] This invention utilizes 3D printing technology to enhance the encoding capability of encrypted information, enabling the encryption of information to become more complex and diverse. This invention does not impose any special limitations on the 3D printing technology, which includes material extrusion 3D printing, electric field-driven jet deposition 3D printing, or electrofluid 3D printing, etc., with the printing pressure maintained at 5–50 kPa and the printing speed at 10–15 mm / s.

[0061] In this invention, in the step of preparing the underlying film by scraping and drying, the drying temperature is 50-100°C, more preferably 50-70°C; in the step of obtaining the cover layer by heating and curing, the heating and curing temperature is 80-100°C, and the heating and curing time is 1-4 hours.

[0062] The technical solution of the present invention will be further described below with reference to specific embodiments.

[0063] Example 1

[0064] This embodiment provides a barcode phase change anti-counterfeiting label film and its preparation method.

[0065] 100g of a 0.8wt% bacterial cellulose aqueous dispersion, 0.94g of graphite powder, and 5.3g of paraffin microcapsules with a paraffin content of 85wt% (phase change temperature of 40℃) were mixed in a beaker and placed in an oil bath at 60℃, and stirred at 500 rpm. After stirring for 4 hours, a phase change slurry was obtained.

[0066] 100g of a 0.8wt% bacterial cellulose aqueous dispersion and 0.2g of graphite powder were uniformly stirred in a magnetic stirrer. A 10cm×10cm film was then coated using a 150μm doctor blade and dried in a 60℃ drying oven to obtain a 40μm thick base film. Using the aforementioned phase change slurry, a 200μm thick barcode containing encrypted information was printed on the base film using a material extrusion 3D printing device. This barcode was then dried in a 60℃ drying oven to complete the writing of the encrypted information, thus constructing an 80μm encrypted information layer.

[0067] 8.5g of polydimethylsiloxane (viscosity 3500cP, the same below) and 1.5g of graphite powder were stirred evenly at 500r / min, and then placed on the bottom film and the encrypted information layer. The mixture was then covered and smoothed using a 150μm scraper. The mixture was then cured in a 90℃ drying oven for 2 hours to obtain a barcode phase change anti-counterfeiting label film with a total thickness of 200μm.

[0068] like Figure 3 As shown, the barcode phase change anti-counterfeiting label film is heated to 45°C, the barcode anti-counterfeiting label is photographed using an infrared camera, and then the information is read from the infrared image using a barcode scanning device.

[0069] Example 2

[0070] This embodiment provides a method for preparing a QR code phase-change anti-counterfeiting label film, the process of which is as follows:

[0071] 100g of a 0.8wt% bacterial cellulose aqueous dispersion, 0.94g of graphene microsheets, and 5.3g of 85wt% paraffin microcapsules (phase change temperature 48℃) were mixed in a beaker and placed in an oil bath at 60℃, and stirred at 500 rpm. After stirring for 4 hours, a phase change slurry was obtained.

[0072] 100g of a 0.8wt% bacterial cellulose aqueous dispersion and 0.2g of graphene microsheets were uniformly stirred in a magnetic stirrer. A 10cm×10cm film was then coated using a 150μm doctor blade and dried in a 60℃ drying oven to obtain a 40μm thick base film. Using the aforementioned phase change slurry, a 200μm thick barcode containing encrypted information was printed on the base film using a material extrusion 3D printing device. This barcode was then dried in a 60℃ drying oven to complete the writing of the encrypted information, resulting in an 80μm encrypted information layer.

[0073] 8.5g of polydimethylsiloxane and 1.5g of graphene microsheets were stirred evenly at 500 rpm and then placed on the bottom film and the encrypted information layer. The mixture was then covered and smoothed using a 150μm scraper. The mixture was then cured in a 90℃ drying oven for 2 hours to obtain a 3D-printed phase-change anti-counterfeiting label with a total thickness of 200μm.

[0074] like Figure 4 As shown, when the QR code phase-change anti-counterfeiting label film is heated to different temperatures and photographed with an infrared camera, the encrypted information cannot be observed at excessively high or low temperatures; it can only be observed within its phase-change temperature range. Figure 5 As shown, the encrypted information is difficult to observe when photographed with a regular camera at 48℃, indicating that the anti-counterfeiting label has good security.

[0075] Example 3

[0076] This embodiment provides a method for preparing a multi-level phase change anti-counterfeiting label film, the process of which is as follows:

[0077] 100g of a 0.8wt% methylcellulose aqueous dispersion, 0.94g of carbon nanotubes, and 5.3g of paraffin microcapsules with a paraffin content of 85wt% (phase change temperature 48℃, high-temperature microcapsules) were mixed in a beaker and placed in an oil bath at 60℃. The mixture was stirred at 500 rpm to obtain a high-temperature phase change slurry. The paraffin microcapsules in the above step were replaced with polyethylene glycol microcapsules with a phase change temperature of 30℃ (low-temperature microcapsules) to prepare a low-temperature phase change slurry.

[0078] 100g of a 0.8wt% aqueous dispersion of methylcellulose and 0.2g of carbon nanotubes were uniformly stirred in a magnetic stirrer. A 10cm × 10cm film was then coated using a 150μm doctor blade and dried in a 60℃ oven to obtain a 40μm thick base film. Encrypted information was then written using a material extrusion 3D printing device. A low-temperature phase change slurry was used to write the first-level encryption information, achieving a thickness of 200μm; a high-temperature phase change slurry was used to write the second-level encryption information, achieving a thickness of 80μm. The layers were then dried in a 60℃ oven to complete the preparation of a multi-level encryption information layer.

[0079] 8.5g of polydimethylsiloxane and 1.5g of carbon nanotubes were stirred evenly at 500r / min and then placed on the bottom film and the encrypted information. The mixture was then covered and smoothed using a 150μm scraper. The mixture was then cured in a 90℃ drying oven for 2 hours to obtain a multi-level phase change anti-counterfeiting label film with a total thickness of 200μm.

[0080] By heating the multi-stage phase change anti-counterfeiting label film to different temperatures and using an infrared camera to photograph the QR code anti-counterfeiting label, it can be clearly observed that different encrypted information can be observed at different temperatures. Figure 6 In the image, 'a' represents an infrared image taken at 35°C. Figure 6 (where b is an infrared image taken at 50℃), which greatly improves the security of the anti-counterfeiting label. The DSC curves of the low-temperature microcapsules, low-temperature phase change slurry, high-temperature microcapsules, and high-temperature phase change slurry used in this multi-level phase change anti-counterfeiting label are shown in the figure. Figure 7 As shown, the first-level anti-counterfeiting zone corresponds to Figure 6 The pattern shown in 'a' corresponds to the secondary anti-counterfeiting zone. Figure 6 The pattern shown in b is an example of the present invention. The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A 3D-printed phase change anti-counterfeiting label, characterized in that, Includes a base film, an encrypted information layer, and a cover layer; The underlying film is a cellulose membrane containing an opaque, thermally conductive filler. The encrypted information layer is obtained by 3D printing a phase change slurry onto a bottom film; the phase change slurry includes phase change microcapsules, cellulose, and opaque thermally conductive filler. The capping layer comprises polydimethylsiloxane and an opaque thermally conductive filler.

2. The 3D-printed phase-change anti-counterfeiting label as described in claim 1, characterized in that, The cellulose of the cellulose membrane of the bottom film and the cellulose of the encryption information layer are selected from one or more of bacterial cellulose, methylcellulose, ethylcellulose, or microfibrillated cellulose.

3. The 3D-printed phase change anti-counterfeiting label as described in claim 1, characterized in that, The opaque thermally conductive filler in the bottom film, the encrypted information layer, and the cover layer is selected from one or more of silicon carbide, graphene microflakes, silicon oxide, graphite powder, carbon nanotubes, beryllium oxide, aluminum nitride, carbon black, or carbon fiber.

4. The 3D-printed phase-change anti-counterfeiting label as described in claim 1, characterized in that, The cellulose type of the cellulose membrane in the bottom film is the same as that in the encryption information layer, and the opaque thermally conductive filler type of the bottom film, the encryption information layer, and the cover layer is the same.

5. The 3D-printed phase-change anti-counterfeiting label as described in claim 1, characterized in that, The phase change microcapsules are selected from one or more of paraffin microcapsules, polyethylene glycol microcapsules, octadecane microcapsules, or eicosane microcapsules.

6. The 3D-printed phase change anti-counterfeiting label as described in claim 1, characterized in that, The phase change slurry comprises 75-85 parts of phase change microcapsules, 5-15 parts of cellulose, and 5-15 parts of opaque thermally conductive filler; the content of opaque thermally conductive filler in the bottom film and the capping layer is 10-30 wt%.

7. The 3D-printed phase-change anti-counterfeiting label as described in claim 1, characterized in that, The thickness of the 3D printed phase change anti-counterfeiting label is 50-250 μm, the thickness of the bottom film is 10-50 μm, and the thickness of the encryption information layer is 1 / 2 to 1 / 3 of the thickness of the 3D printed phase change anti-counterfeiting label.

8. The method for preparing a 3D-printed phase-change anti-counterfeiting label as described in any one of claims 1 to 7, characterized in that, Includes the following steps: A. Disperse an opaque thermally conductive filler in an aqueous cellulose dispersion, and prepare a bottom film by scraping or spin coating and drying. B. Disperse phase change microcapsules and opaque thermally conductive fillers in cellulose aqueous dispersion and stir to mix evenly to obtain phase change slurry; use 3D printing technology to print an encrypted information layer on the surface of the bottom film of the phase change slurry. C. After uniformly mixing the opaque thermally conductive filler and polydimethylsiloxane, coat and smooth the surface of the bottom film and the encrypted information layer, and heat and cure to obtain the cover layer.

9. The preparation method according to claim 8, characterized in that, The concentration of the cellulose aqueous dispersion in steps A and B is 0.5–3 wt%.

10. The preparation method according to claim 8, characterized in that, In the step of preparing the underlying film by scraping or spin coating and drying, the drying temperature is 50-100℃; in the step of obtaining the cover layer by heating and curing, the heating and curing temperature is 80-100℃ and the heating and curing time is 1-4h.

Citation Information

Patent Citations

  • BIM-based floor building integrated assembly system and management method thereof

    CN109166053A

  • Phase-change capsule type thermal camouflage part capable of being coded and preparation method thereof

    CN114822217A